Determinants of Bank Performance in a Developing Country: Evidence From Morocco - El Mehdi Ferrouhi (Organizations and Markets in Emerging Economies, 2017)
This paper aims to define long-term determinants of Moroccan commercial banks performance, for the period 2005-2015, using the Johansen cointegration test. For this purpose, we use bank performance ratios (ROA, ROE and NIM) as dependent variables, and deposits, liquidity ratios, bank-specific and macroeconomic variables as explicative variables. Results obtained show that long-term performance of Moroccan commercial banks depends on deposits, short-term, long-term and funding liquidity, the size of the bank and its square, internal and external funding, deposits interest rates and foreign direct investments. These results show the significance of bank-specific variables as long-term determinants of the performance of Moroccan commercial banks.